Frequency of and risk factors for the surgical resection of nonmalignant colorectal polyps: a population-based study - Le Roy, Florence; Manfredi, Sylvain; Hamonic, Stéphanie; Piette, Christine; Bouguen, Guillaume; Riou, Françoise; Bretagne, Jean-François (Endoscopy, 2016)
Background and study aims: The management of patients with colon polyps who are referred to surgery remains uncharacterized in a population-based setting. The aims of this study were to determine the frequency, risk factors, and outcomes of patients referred for surgical resection of colorectal polyps. Patients and methods: All patients who underwent a colonoscopy for positive fecal occult blood test in the setting of a population-based colorectal cancer screening program in France between 2003 and 2012 were analyzed. The primary outcome was the proportion of patients undergoing colorectal surgery for polyps without invasive carcinoma. Logistic regression analysis was applied to identify risk factors for surgical resection.Results: Among 4251 patients with at least one colorectal polyp, 175 (4.1 %) underwent colorectal surgery. Risk factors for surgery included size, proximal polyp location, advanced histology (villous or high grade dysplasia), the endoscopy center, and colonoscopy performed during the first half of the study period. Subgroup analysis of 3475 colonoscopies performed by 22 endoscopists who performed at least 50 colonoscopies during the study period, identified the endoscopist as an additional risk factor. The adjusted proportions of referrals to surgery ranged from 0 to 46.6 % per endoscopist for polyps ≥ 20 mm (median 20.2 %). Overall, surgical complications occurred in 24.0 %, and one patient died following surgery (0.5 %). None of the 175 patients who underwent surgery were referred to a tertiary endoscopic center prior to surgery. Conclusions: In this population-based study, 4.1 % of patients with nonmalignant polyps were referred for surgical resection. The endoscopist was one important factor that was associated with surgical referral. To further decrease the proportion of inappropriate surgery in patients, endoscopists should refer their patients with large or difficult polyps to expert endoscopists prior to surgery.